Molecular Characteristics of Cassava Carvita 25 Somaclonal Variant Using SSR Marker - Hartati, Hartati; Ramadanti, Nur Ayu; Putri, Dwi Hilda; Hartati, N. Sri (Jurnal ILMU DASAR, 2020)
Cassava is one of the most important food commodities besides rice and corn. Carvita 25 is a somaclonal variation that was induced from Adira IV cassava variety. Our study aimed to analyze the genetic differences of Carvita 25 compared to Adira IV by using SSR markers. Two cassava varieties, Carvita 25 and Adira IV, were used as plant materials and eleven SSRY primers were used to amplifythe fragments of cassava DNA. The results showed that SSRY 151 primer produced the highest polymorphic band (85.71%) where 6 out of 7 alels were polymoprphics with the length size from 120 to 600 bp. Of the total 56 of polymorphic bands, 26 alels were previously present in Adira IV but then it can not be found in Carvita 25, while 30 other bands were new fragments that were previously not present in Adira IV but then were present in Carvita 25. These genetic differencesof both Adira IV and Carvita 25 were also strengthened by the Jacard similarity value. The Jaccard similarity between Carvita 25 and Adira IV were 0.40-0.50, while the similarity between plants of Carvita 25 were 0.79-0.87, and in plants of Adira IV were 0.98- 1.These values showed thewide genetic difference between Adira IV and a somaclonal variation of Carvita 25.Keywords: cassava, Carvita 25, polymorphic, somaclonal variation, SSR Marker.